Предмет: Математика, автор: aazovskaya

Помогите с решением даю 15 баллов

Приложения:

Ответы

Автор ответа: jekadva
1

Ответ:

Пошаговое объяснение:

1) (-6\frac{2}{3} )+(-8,75)+(-2\frac{5}{12} )= -6\frac{2}{3} -8\frac{3}{4} -2\frac{5}{12} =-6\frac{8}{12} -8\frac{9}{12} -2\frac{5}{12} =-(6\frac{8}{12} +8\frac{9}{12} +2\frac{5}{12})=-16\frac{22}{12} =-17\frac{10}{12} =-17\frac{5}{6}

2)(-3\frac{7}{15})+(-0,4)+(-6\frac{1}{3} )= -3\frac{7}{15}-\frac{2}{5} -6\frac{1}{3} =-3\frac{7}{15}-\frac{6}{15} -6\frac{5}{15}=-(3\frac{7}{15}+\frac{6}{15} +6\frac{5}{15})=-9\frac{18}{15} =-10\frac{3}{15}=-10\frac{1}{5}

3)(-1,5)+(-3\frac{4}{5} )+(-8\frac{3}{20} )=-1,5-3,8-8,15=-(1,5+3,8+8,15)=-13,45

4)(-2\frac{5}{8} )+(-9,25)+(-\frac{3}{4} )=-2\frac{5}{8} -9,25-0,75=-(2\frac{5}{8} +9,25+0,75)=-12\frac{5}{8}

Похожие вопросы
Предмет: Математика, автор: oksana198883